Social Dimensions of Cyber Extortion in Social Media;An empirical Study in Karbala Governorate - Jawad Witwit, Ali; Ali Marzouk, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The use of social networking websites is spreading at a breakneck speed across the world; this is supported by the wide spread of modern technologies (smart mobile devices, tablets, iPods, laptops, etc.) and their various applications that enabled individuals to get to know and communicate with capabilities that humans had previously not reached. This has enabled all members of society and all age groups, especially girls and women, in countries of the Middle East, including Iraq; it has allowed the spread of new social values and customs, some of which might contradict the values of the conservative societies to which our young men and women belong. Arab and Islamic societies are conservative societies; however, some men and women users of these devices did not care about that; they did not take into account the social boundaries, customs, traditions, and provisions that define and control their behavior, on the one hand. On the other hand, this expansion in the use of modern communication, and the associated social media, the spread of cybercrime in general and electronic blackmail in particular, devices, whether this cyber extortion is emotional or material, entangled in the traps of perpetrators or cybercriminals, young men and women are victims bound by fear, confusion and isolation, especially in light of the openness that society is witnessing in the midst of what we are witnessing of the expansion of social networking sites and the creation of more of these smart names in a successive way, as the development of modern technology and the dissemination of personal data are the most important factors falling into the trap of electronic extortion, so the main question of research revolves around the following:What are the social dimensions of the crime of cyberextortion?However, several questions arise from the main question, including: What is meant by (extortion)? What exactly is cyberextortion? Is cyberextortion a crime? What is meant by electronic crimes in general? What are the pillars of the crime of cyberextortion? What are its motives? What are the types of electronic extortion crimes, and what are their means? What are its visible effects? Is society affected by these crimes? What is the social group most affected by these crimes? These and other questions that the researcher will try to answer in the course of his study.